National pharmacy associations in the commonwealth: current scenario and future needs to maximise effective contributions of the pharmacy profession towards universal health coverage - Ayesha Iqbal; Victoria Rutter; Gizem Gülpınar; Manjula Halai; Briella Awele; Rasha Abdelsalam Elshenawy; Claire Anderson; Rabia Hussain; Amy Hai Yan Chan (Taylor & Francis Group, 2021)
Background The Commonwealth Pharmacists Association (CPA) is a charity representing pharmacists across the Commonwealth, with the vision of empowering and collaboratively develop the profession and fully utilise the potential of pharmacists to strengthen health systems through supporting better access to, quality and use of medicines and related services. Commonwealth comprises predominantly of low- and middle-income countries, where limited data often exists in pharmacy practice. There is a recognised need across the Commonwealth to focus on developing, implementing and fully utilising pharmacy professional services to progress universal health coverage and achieve the sustainable development goals, particularly in low and middle-income countries; however, currently a knowledge gap exists in understanding the national priorities in Commonwealth nations. CPA is ideally positioned to access to these nations. The aim of this study was thus to explore the priorities and focus areas of NPAs across the Commonwealth and create evidence for a needs-based approach to inform the support that the Commonwealth pharmacists association can collaboratively and strategically provide to its members to progress towards shared goals. Methods Data were collected virtually on Zoom by conducting interviews using a semi-structured interview guide developed for this study with CPA councillors representing NPAs or their equivalents if no official body existed. An inductive, reflexive, thematic analysis was performed for data analysis. Results In total, 30 councillors were interviewed from 30 low- and medium-income countries. The three main overarching priority areas identified across respective Commonwealth nations developing extended pharmacy services, improving pharmacy education, and developing and redefining the role of NPAs. Conclusions This novel study highlights the collective priorities for the pharmacy profession across the low and middle-income countries of the Commonwealth and the urgent need for supporting NPAs around the three identified overarching priority areas. The mapped-out priorities will inform an evidence-based approach for the CPA to better support NPAs in their mission through advocacy and practitioner development, to fully harness pharmacists' unique skill set and maximise their contribution to progressing universal health coverage.